Intelligent skin cancer detection applying autoencoder, MobileNetV2 and spiking neural networks (vol 144, 110714, 2021) - Togacar, Mesut; Comert, Zafer; Ergen, Burhan (Pergamon-Elsevier Science Ltd, 2021)
[Abstract Not Available]